SLOPE STABILITY ANALYSIS OF LIFE OF MINE IN LATERITE, CLAY, AND LIMESTONE MINING OPERATIONS AT PT XYZ IN SOUTH KALIMANTAN - Gymnastiar N.A, Muhammad
PT XYZ is one of the companies engaged in laterite, clay, and limestone mining, holding a mining business permit area (WIUP) in the Province of South Kalimantan. The company conducts open-pit mining activities for laterite soil, clay, and limestone, which will result in the formation of benches on the mine slopes. PT XYZ intends to evaluate the long-term stability of the slopes and optimize slope geometry. Therefore, slope stability analysis is required. The stability analysis for laterite and clay mine slopes is carried out using Slide 2 software, with the probability of failure and the safety factor of the slopes calculated using the Monte-Carlo and Bishop Simplified methods. For the limestone mine, kinematic analysis is conducted using Dips and Rocplan software. The analysis results indicate that for single slopes, both in the cast and waste dump areas of the laterite mine, the lowest static safety factor (SF) is 1.3, with a landslide probability of 0.00%. For overall slope analysis, the lowest static and dynamic SFs are 1.38 and 1.23, respectively. Furthermore, the clay slope analysis shows a static SF of 2 for single slopes, and the lowest overall static and dynamic SFs are 2.0 and 1.8, respectively. However, the analysis results indicate that the slopes are not yet optimal. The optimization of the clay mine slope was then performed by adjusting the slope geometry to a height and angle of 11 m and 80º, yielding a static SF of 1.2 for single slopes and the lowest overall static and dynamic SFs of 2.0 and 1.82. Subsequently, kinematic analysis was performed on the limestone mine to assess potential slope failures caused by joints cutting through the slope. The kinematic analysis showed that wedge failures were the most common, and analytical analysis yielded the lowest SF of 13.7, indicating that the slope is considered safe.